Intervendor Differences in the Accuracy of Detecting Regional Functional Abnormalities: A Report From the EACVI-ASE Strain Standardization Task Force - Mirea, Oana; Pagourelias, Efstathios D; Duchenne, Jurgen; Bogaert, Jan; Thomas, James D; Badano, Luigi P; Voigt, Jens-Uwe (JACC. Cardiovascular imaging, 2018)
The purpose of this study was to compare the accuracy of vendor-specific and independent strain analysis tools to detect regional myocardial function abnormality in a clinical setting. Speckle tracking echocardiography has been considered a promising tool for the quantitative assessment of regional myocardial function. However, the potential differences among speckle tracking software with regard to their accuracy in identifying regional abnormality has not been studied extensively. Sixty-three subjects (5 healthy volunteers and 58 patients) were examined with 7 different ultrasound machines during 5 days. All patients had experienced a previous myocardial infarction, which was characterized by cardiac magnetic resonance with late gadolinium enhancement. Segmental peak systolic (PS), end-systolic (ES) and post-systolic strain (PSS) measurements were obtained with 6 vendor-specific software tools and 2 independent strain analysis tools. Strain parameters were compared between fully scarred and scar-free segments. Receiver-operating characteristic curves testing the ability of strain parameters and derived indexes to discriminate between these segments were compared among vendors. The average strain values calculated for normal segments ranged from -15.1% to -20.7% for PS, -14.9% to -20.6% for ES, and -16.1% to -21.4% for PSS. Significantly lower values of strain (p < 0.05) were found in segments with transmural scar by all vendors, with values ranging from -7.4% to -11.1% for PS, -7.7% to -10.8% for ES, and -10.5% to -14.3% for PSS. Accuracy in identifying transmural scar ranged from acceptable to excellent (area under the curve 0.74 to 0.83 for PS and ES and 0.70 to 0.78 for PSS). Significant differences were found among vendors (p < 0.05). All vendors had a significantly lower accuracy to detect scars in the basal segments compared with scars in the apex (p < 0.05). The accuracy of identifying regional abnormality differs significantly among vendors.